Eksistensi Perpustakaan Di Era Pendemi Covid Dalam Meningkatkan Kunjungan Pemustaka Di Perpustakaan Daerah Kota Mataram - Iskandar Iskandar (JIAP (Jurnal Ilmu Administrasi Publik), 2023)
The existence of libraries in the era of the Covid pandemic is very important to maintain so that the information transformation process continues in society. On that basis, this research was made with the aim of a) To find out the level of user visits in the era of the Covid pandemic, b) To identify the obstacles faced by libraries in increasing user visits. The method used in this research is qualitative with a descriptive approach, with data collection techniques of observation, interviews, interviews, documentation, and literature. The results obtained by researchers in increasing interest in visiting library users during the Covid-19 pandemic at the Mataram City Archives and Library Service, namely a) Promotion of the library b) Procurement of collections c) Strategies for creating excellent service d) Collaboration with the community collection development activities in community leaders e ) Application of health protocols. However, it has constraints, namely the budget which is still lacking in facilities and infrastructure and so on. There are no IT experts yet, and the location is less strategic.